Factors affecting cstomers’ experience in local fast food restaurant - Azila Jaini; Suraya Mahmood; Siti Zamanira Mat Zaib (2014)
Fastest growing number of fast food franchises in Malaysia become a major threat for local fast food to sustain in their business. A case study was conducted to explored factors affecting customers’ experience towards local fast food restaurant in Malaysia. The purpose is to investigate the most important factors that could create positive experience and to identify the elements that influence the customers to go to the restaurant. In this paper, data was collected quantitatively where convenience sampling method was specifically obtained through questionnaires on 364 respondents who dine in at two restaurant outlets. Multiple Regression and Pearson Correlation was applied to analyze four factors, which are food quality, service quality, atmospheric quality, and perceived value that may influence the positive customers’ experience. The results identified that the customers have passion to revisiting these two outlets due to the food quality, service quality and perceived value offered by them. Perceived value shows the highest standardized coefficient level of 0.550 becomes a key driver for creating positive experience toward this restaurant. This study offers the restaurant to increase the understanding on consumer values among their existing and potential customers. All result of this paper was used Predictive Analytics Software PASW version 18.0.